2013
DOI: 10.1038/npp.2013.150
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Crossover Trial of Ketamine in Obsessive-Compulsive Disorder: Proof-of-Concept

Abstract: Serotonin reuptake inhibitors (SRIs), the first-line pharmacological treatment for obsessive-compulsive disorder (OCD), have two limitations: incomplete symptom relief and 2-3 months lag time before clinically meaningful improvement. New medications with faster onset are needed. As converging evidence suggests a role for the glutamate system in the pathophysiology of OCD, we tested whether a single dose of ketamine, a non-competitive N-methyl-D-aspartate (NMDA) glutamate receptor antagonist, could achieve rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
204
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(228 citation statements)
references
References 58 publications
7
204
2
2
Order By: Relevance
“…6 Specifically, rapastinel did not increase psychotomimetic effects following dosing in this sample of OCD patients, unlike ketamine in prior studies. 1,[3][4][5] In this small open-label sample, rapastinel had acute effects on obsessions and compulsions, anxiety and depression. However, rapastinel did not have significant effects on OCD symptoms one week post-infusion.…”
Section: Conclusion/discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…6 Specifically, rapastinel did not increase psychotomimetic effects following dosing in this sample of OCD patients, unlike ketamine in prior studies. 1,[3][4][5] In this small open-label sample, rapastinel had acute effects on obsessions and compulsions, anxiety and depression. However, rapastinel did not have significant effects on OCD symptoms one week post-infusion.…”
Section: Conclusion/discussionmentioning
confidence: 73%
“…To have clinical utility, glutamate modulators should refine molecular targets for rapid and sustained action while minimizing side effects. Mechanistic preclinical data suggests drugs like rapastinel 17 and ketamine's metabolite hydroxynorketamine 1,8 that act on AMPA receptor modulation pathways may be promising therapeutic strategies.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…La ketamina, otro antagonista no competitivo de los receptores NMDA, administrada vía EV reduce significativamente los síntomas obsesivo-compulsivos en ausencia de ISRS, de acuerdo a un estudio controlado con placebo; la mejoría ocurre en minutos y se mantiene al menos 1 semana luego de la infusión (50). Asimismo, un reporte de caso sugiere que la ketamina es útil en TOC refractario y produce un efecto máximo a partir de los 30 min de iniciada la infusión (51).…”
Section: Fármacos Relacionados a La Función Glutamatérgicaunclassified
“…One study [15] reported that there were more sexual, aggressive, and religious obsessions in responders of a memantine augmentation trial. Further support for the glutamatergic system playing a role in the development of OCD symptoms arises from studies showing the effectiveness of ketamine in rapidly reducing OCD symptoms [16]. The studies are too small to determine which participants respond to the treatment and which participants do not.…”
Section: Predictors Of Response To Other Psychotropic Agentsmentioning
confidence: 99%